Inquisitive Ability on Chemistry Material Gamification with Project Based Learning Approach - Santhya Anaomi Tamansa; Nelius Harefa; Riris Marito Tamba (Universitas Negeri Medan, 2024)
This study aims to evaluate the use of gamification in increasing students’ inquisitive ability on chemistry material with project based learning approach. In this research, an analysis of students' inquisitive ability will be carried out which consists of three indicators, namely wondering and questioning, exploring and investigating, and challenging assumption. The research was carried out using a classroom action research approach consisting of 3 cycles, where research data was collected by giving a questionnaire consisting of 4 statements for each indicator with 5 options for each research instrument. Apart from the questionnaire method, research data was collected through random interviews and structured observation. Based on data analysis, students' inquisitive ability was highest in the wondering and questioning indicator at 83.68 in cycle 3. Meanwhile, students' inquisitive ability was lowest in the challenging assumptions indicator at 41.25 in cycle 1. In general, gamification activities were able to increase students' inquisitive ability between 9% - 50%.